Le corps de Roland Barthes - Loba, Mirosław (Studia Romanica Posnaniensia, 2010)
The aim of this paper is to present the relationship between body and linguistic and literary signs in the work of Roland Barthes. The main problem is Roland Barthes thinking on semiotic representation of the body as an ambivalent process of selfconstruction and alienation